Joint downlink and uplink resource allocation for multi-carrier SWIPT system - Miao CUI; Xin YU; Xueyi LI; Guangchi ZHANG; Yijun LIU; Fan LIN (Tongxin xuebao)
A multi-carrier simultaneous wireless information and power transfer (SWIPT) communication system including one base station (BS) and one user was investigated,where both uplink and downlink adopt orthogonal frequency division multiplexing (OFDM).In the downlink,the BS transmited information and power to the user simultaneously.In the uplink,the user transmited information to the BS by using the power harvested from the BS in the downlink.The weighted sum of the downlink and uplink achievable rates by jointly optimizing subcarrier allocation and power allocation of the uplink and downlink were aimed to maximized.An optimal algorithm to solve the joint resource allocation problem was proposed,which was based on the Lagrange duality method and the ellipsoid method.Finally,the result shows the performances of the proposed algorithm by computer simulations.